The Eight-Chop Technique in Nonagenarian Patients: Real-World Intraoperative and Postoperative Outcomes - Tsuyoshi Sato (Journal of Clinical Medicine, 2026)
Objectives: To describe intraoperative and postoperative outcomes of the Eight-Chop Technique in elderly patients, with particular attention to nonagenarian patients undergoing cataract surgery. Methods: This retrospective study included consecutive eligible eyes undergoing Eight-Chop phacoemulsification and posterior chamber intraocular lens implantation at a single clinic. Eyes were stratified by age at surgery into 70–79 years, 80–89 years, and ≥90 years groups. Sixty eyes were included in each younger group, and all 49 eligible nonagenarian eyes were included. Eyes were not intentionally excluded from the younger groups because of poor pupillary dilation, zonular weakness, white cataract, pseudoexfoliation, glaucoma, age-related macular degeneration, or advanced nuclear grade. Preoperative characteristics, intraoperative parameters, best-corrected visual acuity (BCVA), intraocular pressure, and corneal endothelial cell density (CECD) were evaluated. Linear mixed-effects models accounted for fellow-eye correlation. Results: A total of 169 eyes were analyzed. The ≥90-year cohort had greater baseline complexity; intraoperative differences were descriptive, with the highest operative time, phacoemulsification time, aspiration time, cumulative dissipated energy, and irrigation fluid volume (all p < 0.001). Postoperative BCVA improved from baseline in all groups. Mean CECD loss at 19 weeks was −1.3 ± 5.7%, −0.7 ± 5.7%, and 3.5 ± 9.2% in the 70–79-, 80–89-, and ≥90-year groups, respectively. No serious intraoperative complications occurred. Conclusions: The Eight-Chop Technique was used across elderly age groups, including nonagenarian patients. Observed age-group differences represent associations in this retrospective dataset and do not establish causal age effects or comparative superiority, safety, or endothelial protection of the technique.